Viral Etiologies of Acute Dehydrating Gastroenteritis in Pakistani Children: Confounding Role of Parechoviruses - Alam, Muhammad Masroor (Viruses, 2015)
Despite substantial interventions in the understanding and case management of acute gastroenteritis, diarrheal diseases are still responsible for a notable amount of childhood deaths. Although the rotavirus is known to cause a considerable burden of pediatric diarrheal cases, the roles of other viruses remain undefined for the Pakistani population. This study was based on tertiary care hospital surveillance, from January 2009 to December 2010, including the detection of rotavirus, norovirus, astrovirus, and human parechovirus in children under the age of five using serological or molecular assays. Rotavirus, human parechovirus, norovirus, and astrovirus were detected in 66%, 21%, 19.5%, and 8.5% subjects, respectively. Human parechovirus genotypes, determined through analysis of VP1 gene sequences, showed a great diversity among co-circulating strains. Eighty percent of hospitalized children had dual or multiple viral infections, while 98% parechovirus positive cases were co-infected with rotavirus. The remarkable diversity of viruses associated with the childhood diarrhea in Pakistan calls for large-scale epidemiological surveys, coupled with case control studies, to ascertain their role in clinical manifestations. In addition, these findings also highlight the need for the implementation of up-to-date health interventions, such as the inclusion of a rotavirus vaccine in routine immunization programs for the improvement of quality in child health care.